The Gut Microbiome of Pediatric Crohn's Disease Patients Differs from Healthy Controls in Genes That Can Influence the Balance Between a Healthy and Dysregulated Immune Response. Issue 11 (November 2016) - Dunn, Katherine A.; Moore-Connors, Jessica; MacIntyre, Brad; Stadnyk, Andrew; Thomas, Nikhil A.; Noble, Angela; Mahdi, Gamal; Rashid, Mohsin; Otley, Anthony R.; Bielawski, Joseph P.; Van Limbergen, Johan
Abstract : Background: Exclusive enteral nutrition (EEN) is a first-line therapy in pediatric Crohn's disease (CD) thought to induce remission through changes in the gut microbiome. With microbiome assessment largely focused on microbial taxonomy and diversity, it remains unclear to what extent EEN induces functional changes that thereby contribute to its therapeutic effect. Methods: Fecal samples were collected from 15 pediatric CD patients prior to and after EEN treatment, as well as from 5 healthy controls. Metagenomic data were obtained via next-generation sequencing, and nonhuman reads were mapped to KEGG pathways, where possible. Pathway abundance was compared between CD patients and controls, and between CD patients that sustained remission (SR) and those that did not sustain remission (NSR). Results: Of 132 KEGG pathways identified, 8 pathways differed significantly between baseline CD patients and controls. Examination of these eight pathways showed SR patients had greater similarity to controls than NSR patients in all cases. Pathways fell into one of three groups: 1) no prior connection to IBD, 2) previously reported connection to IBD, and 3) known roles in innate immunity and immunoregulation. Conclusions: The microbiota of CD patients and controls represent alternative ecological states that have broad differences in functional capabilities, including xenobiotic and environmental pollutant degradation, succinate metavolism, and bacterial HtpG, all of which can affect barrier integrity and immune regulation. Moreover, our finding that SR patients were more similar to healthy controls suggests that community microbial function, as inferred from fecal microbiomes, could serve as a valuable diagnostic tool. Abstract : Supplemental Digital Content is Available in the Text.Article first published online 11 October 2016.